2019
DOI: 10.1177/1024258919847313
|View full text |Cite
|
Sign up to set email alerts
|

The calculation of a living wage: the UK’s experience

Abstract: Translating the concept of a living wage into a cash figure presents a number of challenges. A recent review of the approaches used in the UK explored these, with the aim of creating a unified and improved calculation. Designing a living wage relies on some technical decisions, such as which data sources are most appropriate. But many of the building blocks underlying a living wage require judgements on societal values, expectations and norms. The living wage rates in the UK are voluntary and promoted by campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 3 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…The methodology focuses solely on the 'basket of goods' approach; the poverty line reference point has been dropped. Crucially, however, acceptable living costs are established through dialogue with workers and families (see D'Arcy and Finch, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology focuses solely on the 'basket of goods' approach; the poverty line reference point has been dropped. Crucially, however, acceptable living costs are established through dialogue with workers and families (see D'Arcy and Finch, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Luther was paid £17,000 a year, but often worked 60-hour weeks – commensurate to £5.49 an hour, compared with the £7.20 NLW rate at the time. Similarly, while Sebastián’s (chef, Last Boutique Hotel) annual salary of £28,200 was higher than the average chef salary at the time (£18,640), his 70-hour week translated into an hourly rate of just £7.75, below the recommended London Living Wage of £9.75 per hour in 2015 (D’Arcy and Finch, 2016). These examples are supported by findings from a 2016 members’ survey by the trade union Unite, which found that 44% of chefs worked an average of 48 to 60 hours weekly, while 14% worked over 60 hours (Unite, 2016).…”
Section: The Dynamics Of Wage Theft In Hotels: Empirical Findingsmentioning
confidence: 99%
“…There are two living wage rates (one for London and one for the rest of the country), which are determined and regularly adjusted by the Living Wage Foundation, an organisation supported by trade unions and various other social organisations, as well as by some private companies (https://www.livingwage.org.uk). The calculation of living wages is based on a sophisticated methodology that regularly analyses the 'real costs of living' (D'Arcy and Finch, 2019). The current UK living wage rate is about 10 per cent higher than the national minimum wage, while the London rate is nearly 30 per cent higher.…”
Section: Recent Initiatives For Living Wages In Europementioning
confidence: 99%